2013
DOI: 10.1002/ggge.20188
|View full text |Cite
|
Sign up to set email alerts
|

Major and trace element composition of the high 3He/4He mantle: Implications for the composition of a nonchonditic Earth

Abstract: [1] The bulk composition of the silicate portion of the Earth (BSE) has long been assumed to be tied to chondrites, in which refractory, lithophile elements like Sm and Nd exist in chondritic relative abundances. However, the Nd from 0.51263 (chondritic) to 0.51300. The new BSE composition is depleted in highly incompatible elements, including K, relative to the chondrite-based BSE, and offers a solution the ''missing '' 40 Ar paradox. This BSE compositional model requires that >83% of the mantle is deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 120 publications
(337 reference statements)
2
50
0
Order By: Relevance
“…7). Using the most recently reported trace element compositions for the peridotite components, we modeled the partial melting of mixtures consisting of DMM (Workman and Hart, 2005) or non-chondritic primitive mantle (Jackson and Jellinek, 2013) and subduction-modified MORB (sm-MORB 2; cf. Fig.…”
Section: Nature Of the Peridotitic Mantle Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Using the most recently reported trace element compositions for the peridotite components, we modeled the partial melting of mixtures consisting of DMM (Workman and Hart, 2005) or non-chondritic primitive mantle (Jackson and Jellinek, 2013) and subduction-modified MORB (sm-MORB 2; cf. Fig.…”
Section: Nature Of the Peridotitic Mantle Componentmentioning
confidence: 99%
“…Fig. 6), DMM (Workman and Hart, 2005), non-chondritic primitive mantle (NCPM; Jackson and Jellinek, 2013), peridotite component mixtures with sm-MORB 2 (cf. Fig.…”
mentioning
confidence: 99%
“…Others have calculated somewhat lower, but still very significant depletions. Jackson and Jellinek (2013) calculated concentrations for the most incompatible elements, including Th and U, that are a little more than 30 % lower than the McDonough and Sun values (Fig. 9.2).…”
Section: Whither Primitive Mantle?mentioning
confidence: 62%
“…After accounting for the amount likely to be in the continental crust or the depleted mantle reservoir, they concluded that 25 % or more of the Earth's 40 Ar inventory was stored in an undegassed or primitive deep mantle. However, using K abundances estimated by Lyubetskaya and Korenaga (2007), (White, 2013), or Jackson and Jellinek (2013), all or nearly all of the Earth's 40 Ar can be accounted for by the atmospheric, crustal, and depleted mantle reservoirs.…”
Section: Whither Primitive Mantle?mentioning
confidence: 99%
See 1 more Smart Citation